2005
DOI: 10.1115/1.2132370
|View full text |Cite
|
Sign up to set email alerts
|

3D Finite Element Model of Meniscectomy: Changes in Joint Contact Behavior

Abstract: The goal of this study is to quantify changes in knee joint contact behavior following varying degrees of the medial partial meniscectomy. A previously validated 3D finite element model was used to simulate 11 different meniscectomies. The accompanying changes in the contact pressure on the superior surface of the menisci and tibial plateau were quantified as was the axial strain in the menisci and articular cartilage. The percentage of medial meniscus removed was linearly correlated with maximum contact press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
139
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 33 publications
5
139
0
Order By: Relevance
“…It has been shown that under this condition, the biphasic response of cartilage can be negligible and the single-phase linear isotropic constitutive law be applicable [40,41]. Therefore, cartilage was modeled as a homogeneous, elastic, linearly isotropic material [1,2,[4][5][6][7]9,16,23,25,30,32,33,[35][36][37][38][39][42][43][44][45][46] with a modulus of 15 MPa [4,9,25,30,35,45] and a Poisson's ratio of 0.46 [31][32][33]47,48].…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that under this condition, the biphasic response of cartilage can be negligible and the single-phase linear isotropic constitutive law be applicable [40,41]. Therefore, cartilage was modeled as a homogeneous, elastic, linearly isotropic material [1,2,[4][5][6][7]9,16,23,25,30,32,33,[35][36][37][38][39][42][43][44][45][46] with a modulus of 15 MPa [4,9,25,30,35,45] and a Poisson's ratio of 0.46 [31][32][33]47,48].…”
Section: Materials Propertiesmentioning
confidence: 99%
“…The femur and tibia were modeled as rigid structures, which greatly reduced the computational time and has been shown to have minimal effect on the model predictions [1,4,6,9,23,[29][30][31][32][33][34][35][36][37][38][39]. Articular cartilage is known to be an anisotropic, biphasic material with a time constant approaching 1500 s [40,41].…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Menisci were modeled as isotropic (Peña et al, 2005(Peña et al, , 2006(Peña et al, , 2008, transversely isotropic (Haut Donahue et al, 2002) or fiber-reinforced linearly elastic solid (Penrose et al, 2002;Shirazi et al, 2008). Example case studies are: knee joint under compression (Bendjaballah et al, 1995;Shirazi et al, 2008), knee joint in combined loading (Peña et al, 2006;Shirazi & Shirazi-Adl, 2009), effect of meniscectomies (Peña et al, 2005(Peña et al, , 2008Yang et al, 2009;Zielinska & Donahue, 2006) and effect of ligament reconstruction on the knee joint biomechanics (Shirazi & Shirazi-Adl, 2009;Suggs et al, 2003). Although fluid flow is believed to play a substantial role in the load response of the knee, little information is known about the fluid pressurization in cartilages and menisci in the real knee contact configuration.…”
Section: Anatomically Accurate Knee Modelingmentioning
confidence: 99%
“…Meniscectomy causes instability to the knee joint with an increased risk of OA [5]. Partial meniscectomy has been reported to increase the risk for the onset of OA by increasing stress and strain in the articular cartilage [6]. The external medial tibial cartilage is vulnerable to thinning once the meniscus extrudes and its surface is in direct, non-physiological, cartilage-cartilage contact with femur [7].…”
Section: Introductionmentioning
confidence: 99%